Analysis of product quality, relationship marketing, and customer satisfaction on b2b towards repurchase intention (case study: Cv. Primadona & Co) - Ali, Alwi; Kusumawati, Nurrani (Journal of Business and Management, 2020)
Abstract. Based on data from the Ministry of Industry (2016), Indonesia has 183 export companies that own the commodity Charcoal. Including CV Primadona & Co. In 30 years in the charcoal commodity CV Primadona & Co experienced ups and downs in the world of international business. The problem is customers who do not want to repurchase and business in Indonesia has experienced very rapid progress. This makes the company have decreased revenue since the last 6 years. In terms of data collection methods, this research is classified as qualitative using in-depth interviews as a means to gather the data. Observation are applied to collect the data. For B2B, the study would be more straightforward because of the use of in-depth interviews to identify and clarify the secret issues in phenomena that are difficult to fully understand. To collect qualitative data, interviews were conducted with 20 companies that have ever bought at Cv. Primadona & Co. The company is located in Korea, Europe and the Middle East. Important factors for repurchasing are demand on the market, quality, price, service, quick response. Some companies have already had the best quality, had a marketing relationship, and have received satisfaction from purchasing. Demand depends on the needs of each country. Quality can be seen from the burning that doesn’t emit sparkles, can withstand burning up to 3 to 5 hours, and no white ash. Customers look for the cheapest price to buy. Satisfying services such as after sales service and guaranteed products become the power to attract customers to repurchase.Keywords: Customer Satisfaction, Product Quality, Relationship Marketing, Repurchase Intention